Analisis SWOT Terhadap Strategi Pemasaran Usaha Mikro Kecil dan Menengah (UMKM) Sentra Industri Gitar dalam Menghadapi Covid-19 - Wahyu Broto Sekti; Rendra Armayana (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The purpose of this research is to find the factors about the strength, weakness, opportunity, and treath of guitar industry centre UMKM Mancasan Village as well as knowing marketing strategies by used marketing mix involve 4P (Product, Price, Promotion, and Place). These papers used research methods of descriptive kualitative with analytical data technique used SWOT analysis. SWOT Analysis is done by identifying and analyzing the internal and external factors that influence the basic component of the guitar industry centre UMKM Mancasan Village. Guitars industry center UMKM Mancasan Village has'nt been maximal in implementing the marketing mix 4P accompanied by analysis SWOT. So that their application needs to be enhanced the marketing of industry centre UMKM Mancasan Village has been maximal.